A study of mathematical thoughts in the geometrical design of Bertam (wild Bornean sago) weaving / Wan Norliza Wan Bakar, Masnira Ramli and Fuziatul Norsyiha Ahmad Shukri - Wan Bakar, Wan Norliza; Ramli, Masnira; Ahmad Shukri, Fuziatul Norsyiha (2013)
Kelarai, a design for weaving, which is made up of various motifs can be produced by a variety of natural products. The main focus of the study is on Kelarai Bertam which is selected based on the firm and robust quality of the wood which was often used as the building materials of traditional houses. The objective of the study is to investigate the geometrical design in the weaving art of Kelarai Bertam, the stimulation of mathematical thoughts in geometrical designs and the evolution of geometrical designs in the weaving art of Kelarai Bertam. The research method utilized in the study was the triangulations method consisting of observation, interview and analysis. The findings revealed that symmetrical forms such as reflection, translation, rotation were present in the wearing of Kelarai Bertam. It is suggested that extensive research can be conducted on the combination of different weaving materials such as wild bertam and bamboo.